The Development Of Eglish Instructional Design Social Learning Network (SLN)-Based Using Auction (Interestedbased Negotiation) Strategy - Muhammad As’at; Punaji Setyosari; Saida Ulfa (Jurnal Inovasi dan Teknologi Pembelajaran, 2018)
Abstract: The purpose of the research is to create an English instructional design social learning network (SLN)-based platform Edmodo using Auction (interested based negotiation) strategy. It can be one of the creative solutions to overcome a limited time in English learning process in a lesson plan package. The method of developing is used in this research is Lee & Owen (2004). The 5 development steps are as follow : 1) analysis; 2) design; 3) development; 4) implementation; 5) evaluation. The product was evaluated by the experts which is the average is 89,3% and 24 students from Indonesian Air Force Abd Saleh Language School Malang is 89,8%. In conclusion, the product is completely valid and could be implemented in learning proses.